Channel carrying: a novel handoff scheme for mobile cellular networks - Junyi Li; Shroff, N.B.; Chong, E.K.P. (IEEE/ACM transactions on networking, 1999)
We present a new scheme that addresses the call handoff problem in mobile cellular networks. Efficiently solving the handoff problem is important for guaranteeing quality of service to already admitted calls in the network. Our scheme is based on a new approach called channel carrying: when a mobile user moves from one cell to another, render certain mobility conditions, the user is allowed to carry its current channel into the new cell. We propose a new channel assignment scheme to ensure that this movement of channels will not lead to any extra co-channel interference or channel locking. In our scheme, the mobility of channels relies entirely on localized information, and no global coordination is required. Therefore, the scheme is simple and easy to implement. We further develop a hybrid channel carrying scheme that allows us to maximize performance under various constraints.